PENGELOLAAN RESIKO PADA ORGANISASI LEMBAGA PERKREDITAN DESA (LPD) (Studi Kasus: LPD Desa Ketewel, Kecamatan Sukawati, Kabupaten Gianyar, Provinsi Bali.) - Pratama Putra, IB. Bima (CITIZEN CHARTER, 2014)
ABSTRACT The aimof the present studywas to investigatehow thw risk management work in LPD. This study made use qualitativeresearchmethods. The data collection methodused inthis studywas field researchmethod. Furthermore, based on this research, the indicators of risk management tecnique by Hanafi are very important in order to determine how the risk management tecnique applied in Lembaga Perkreditan Desa (Village Finance Institution) problem formulation of this scientific paper were taken by field research in LPD Ketewel, Sukawati sub distric, Gianyar regency. Keywords:Risk Management, LPD